2019
DOI: 10.3390/cancers11060848
|View full text |Cite
|
Sign up to set email alerts
|

A New Strategy for Glioblastoma Treatment: In Vitro and In Vivo Preclinical Characterization of Si306, a Pyrazolo[3,4-d]Pyrimidine Dual Src/P-Glycoprotein Inhibitor

Abstract: Overexpression of P-glycoprotein (P-gp) and other ATP-binding cassette (ABC) transporters in multidrug resistant (MDR) cancer cells is responsible for the reduction of intracellular drug accumulation, thus decreasing the efficacy of chemotherapeutics. P-gp is also found at endothelial cells’ membrane of the blood-brain barrier, where it limits drug delivery to central nervous system (CNS) tumors. We have previously developed a set of pyrazolo[3,4-d]pyrimidines and their prodrugs as novel Src tyrosine kinase in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
57
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(60 citation statements)
references
References 79 publications
2
57
0
1
Order By: Relevance
“…Novel small molecule compounds with a pyrazolo [3,4-d]pyrimidine scaffold, Si306 and its prodrug pro-Si306, are ATP-competitive tyrosine kinase inhibitors and can be used to inhibit SFKs [26,27]. A number of pyrazolo [3,4-d]pyrimidines already showed considerable anti-cancer activity in vitro against a number of GBM [14,28,29] and other cancer cell lines [30][31][32][33][34][35][36][37][38][39], as well as in vivo [35,39,40]. We previously reported that Si306 in combination with radiotherapy significantly inhibited the growth of human GBM U87 cell line xenografts in nude mice compared to the control and single treatment [40].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Novel small molecule compounds with a pyrazolo [3,4-d]pyrimidine scaffold, Si306 and its prodrug pro-Si306, are ATP-competitive tyrosine kinase inhibitors and can be used to inhibit SFKs [26,27]. A number of pyrazolo [3,4-d]pyrimidines already showed considerable anti-cancer activity in vitro against a number of GBM [14,28,29] and other cancer cell lines [30][31][32][33][34][35][36][37][38][39], as well as in vivo [35,39,40]. We previously reported that Si306 in combination with radiotherapy significantly inhibited the growth of human GBM U87 cell line xenografts in nude mice compared to the control and single treatment [40].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, pro-Si306 showed enhanced solubility and efficacy in an orthotopic model of GBM compared to Si306. Besides their ability to pass the BBB, Si306 and pro-Si306 successfully, in a dose-dependent manner, inhibited the function of P-glycoprotein (P-gp), an ATP-binding cassette (ABC) transporter member highly expressed in multidrug resistant (MDR) cancer cells [28]. As a result, these compounds showed the ability to reverse paclitaxel resistance in MDR glioblastoma U87-TxR cells [28].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A new SRC inhibitor, belonging to the pyrazolo[3¨ -d] pyrimidines series (i.e., Si306, Lead Discovery Siena, Italy) showed an excellent pharmacodynamic profile and was able to significantly inhibit GBM cell growth in highly P-gp expressing cells as compared to dasatinib [ 116 ]. We previously demonstrated that Si306 showed a synergic radiosensitive effect with proton irradiation in GBM cell lines [ 117 ].…”
Section: New Frontiers To Improve Radiotherapy: Evaluating the Potmentioning
confidence: 99%